Akidah Sayyid Qutb (1906-1966) dan Penafsiran Sastrawi terhadap al-Qur’an - Yusuf Rahman (Universitas Darussalam Gontor, 2011)
This article discusses the ideology of Sayyid Qutb and how this ideology has influenced his approach to the Qur’an. Although, in the beginning of his life he saw the Qur’an as the literary text and hence the literary approach to the Qur’an is the preferred approach, in his later life – when he became Islamist – he revised this approach and treat the Qur’an as a political document. Because of this political interpretation of the Qur’an, his tafsir Fi Zilal al-Qur’an has influenced many radical groups in Egypt and other countries. The primary sources of this article are Sayyid Qutb’s works, especially al-Taswir al-Fanni fi alQur’an, Masyahid al-Qiyamah fi al-Qur’an, and Fi Zilal al-Qur’an. These works are read chronologically and historically to see the development of Qutb’s thought and the shifting of his ideology. Thus, the knowledge of the social-historical and political context of Egypt is important to determine its influence to Qutb and vice versa. Finally, this article concludes that Qutb’s literary approach to the Qur’an has been transformed into ideological and political approach. This shifting is due to the changing of Sayyid’s Qutb worldview, from a secular Muslim to be an ideological one. Furthermore, at the end of his life, he became a theoretical ideological Islamist.